Hepatocyte Growth Factor Overexpression Slows the Progression of 4NQO-Induced Oral Tumorigenesis - He, Xiaoxi; Chen, Si; Tang, Yinghua; Zhao, Xiaomin; Yan, Liting; Wu, Lihong; Wu, Zhicong; Liu, Weijia; Chen, Xinming; Wang, Xinhong (Frontiers in Oncology, 2021)
Objectives: To investigate the role of hepatocyte growth factor (HGF)/c-Met signalling in oral malignant transformation. Methods: We used immunohistochemistry to investigate HGF and c-Met expression in 53 Oral squamous cell carcinoma (OSCC) specimens and 21 adjacent nontumour specimens and evaluated the associations between HGF and c-Met expression and clinicopathological parameters. Additionally, HGF-overexpression transgenic (HGF-Tg) and wild-type (Wt) mice were treated with 4-nitroquinoline-1-oxide (4NQO) to induce oral carcinogenesis for 16 weeks. At 16, 20 and 24 weeks, tongue lesions were collected for clinical observation; estimation of HGF, c-Met, and PCNA expression; apoptosis (TUNEL) assays; and RNA sequencing (RNA-seq). Results: HGF and c-Met were positively expressed in 92.5% and 64% of OSCC samples, respectively. High HGF expression was significantly associated with smaller tumour size (p=0.006) and inferior TNM stage (p=0.032). No correlation between HGF and c-Met levels and other clinical parameters or prognosis was noted. In addition, HGF and c-Met expression was elevated in 4NQO-induced lesions of Wt mice. Compared with Wt mice, HGF-Tg mice have lower tumour incidence, number, volume and lesion grade. In addition, the percentage of PCNA-positive cells in Wt mice was significantly higher than that in HGF-Tg mice at different time points. At 16 weeks, HGF-Tg mice exhibited less apoptotic cells compared with Wt mice (p<0.000), and these levels gradually increased until the levels were greater than that of Wt mice at 24 weeks (p<0.000). RNA-seq data revealed that 140 genes were upregulated and 137 genes were downregulated in HGF-Tg mice. KEGG enrichment analysis showed that upregulated differentially expressed genes (DEGs) are highly correlated with oxidative and metabolic signalling and that downregulated DEGs are related to MAPK and PI3K-AKT signalling. Conclusions: HGF and c-Met expression is upregulated in OSCC tissues and is associated with the occurrence and development of OSCC. HGF overexpression in normal oral epithelial tissue can inhibit 4NQO-induced tumorigenesis potentially through inhibiting proliferation and accelerating apoptosis via MAPK and PI3K-AKT signallings. Key words: OSCC; HGF; c-Met; 4NQO; Tumorigenesis; Transgenic mouse